Anxiety in HIV Patients During Treatment: The Role of Mindfulness and Resilience - Pratitis, Niken Titi; Suryo W , Lutfi (Universitas Ahmad Dahlan, 2025)
HIV remains a significant global health concern, often increasing the risk of psychological distress, including depression and anxiety. Anxiety, characterized by feelings of unease and excessive worry about future events, may be influenced by mindfulness and resilience. Mindfulness, which enhances present-moment awareness, has been shown to reduce anxiety, while resilience enables individuals to cope with stressors, facilitating better management of life and treatment. This quantitative correlational study involved 116 respondents, selected through saturated sampling. The study utilized Nevid et al.'s (2003) Anxiety Scale, Baer et al.'s (2006) Mindfulness Scale, and Reivich & Shatté's (2002) Resilience Scale. The results revealed a significant negative correlation between resilience, mindfulness, and anxiety (F = 20.473, p < 0.05), with these variables accounting for 26.6% of the variance in anxiety levels. Specifically, resilience negatively correlated with anxiety (t = -2.267, p = 0.025), as did mindfulness (t = -3.068, p = 0.003). These findings suggest that both resilience and mindfulness play a crucial role in reducing anxiety among HIV patients. Therefore, integrating mindfulness and resilience-based interventions into HIV care programs may be beneficial in alleviating anxiety in this population.